Enhancement of Signal‐to‐Background Ratio in Molecular Vibrational Signal Extraction by Stimulated Emission Depletion Mechanism - Ge Wang; Lizhen Chen; Qiuqiang Zhan; Guangyou Fang; Yisen Wang (Advanced Photonics Research)
Herein, a novel approach is presented to mitigate the fluorescence interference during the detection of vibrational signal via the stimulated emission depletion (STED). STED is the mechanism commonly employed in optical imaging; however, its application should not be confined solely to this field. To explore additional possibilities, a novel application of STED in vibrational spectroscopy detection is introduced. Vibrational spectroscopy is a widely used technique for the material detection and identification, but its sensitivity is influenced by impurity signals, especially the fluorescence. The proposed method is capable of suppressing fluorescence without influencing vibrational signal. At the low concentration of fluorescent impurities, the signal‐to‐background ratio of vibrational spectroscopy is 2.6 times as high as that without this method. The introduction of depletion light can enhance the detection of vibrational signals, resulting in more optimal signal detection. A promising new application of STED other than super‐resolution imaging is investigated.